Predictors of recurrence in early stage oral tongue squamous cell carcinoma - Chandrashekar Mani; G Lakshminarayana; Ann Kurian; Annapurneshwari (Wolters Kluwer Medknow Publications, 2015)
Introduction: Many histopathological parameters in oral tongue squamous cell carcinoma (OTSCC) have been identified as predictive factors. Certain tumor-related factors increase the risk of nodal metastasis, and many pathological factors affect survival. Objective: The objective of this study is to identify that tumor-related histopathological prognostic factors that can predict recurrence and potentially influence the decision for adjuvant radiotherapy in early stage OTSCC. Materials and Methods: A total of 51 patients who underwent surgery for early stage OTSCC (stage I, II) from 2007 to 2013 were selected. Demographic and clinical details were retrieved. Histopathological reports were reviewed for the following parameters-Margin status (close <5 mm, positive - Invasive squamous cell carcinoma [SCC], carcinoma in situ, marked dysplasia), microscopic depth of invasion, skeletal muscle infiltration (SMI), tumor differentiation, perineural invasion, lymphovascular invasion. Overall survival and recurrence-free survival (RFS) were calculated using the Kaplan-Meier method. Predictors of recurrence were identified using Univariate analysis. Results: Median follow-up was 22 months (range, 5-89 months), the overall survival and RFS were 88% and 81% respectively. The recurrence rate was 19.5% during this time period. The only significant predictor of recurrence in pathologically early stage OTSCC was SMI (P = 0.003) on univariate analysis. Eighty-seven percentage of the recurrences in our study occurred within the 1 st year, with a disease specific mortality rate of 12.5%. Conclusion: In early stage OTSCC, Failure occurred predominantly in patients who had SMI.